2017
DOI: 10.18632/oncotarget.22448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cilostazol on plasma levels of proprotein convertase subtilisin/kexin type 9

Abstract: The protein complex proprotein convertase subtilisin/kexin type 9 (PCSK9) serves as an important target for the prevention and treatment of atherosclerosis and lipid homeostasis. This study investigated the effect of cilostazol on plasma PCSK9 concentrations. We performed a post hoc analysis of two prospective, double-blind, randomized controlled trials including 115 patients of whom 61 received cilostazol 200 mg/day and 54 received placebo for 12 weeks. Linear regression analysis was performed to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A previous study demonstrated the diverse effects of adipoR activation on PCSK9 expression in apoE-deficient (apoE −/− ) mice and wild-type mice [ 17 ]. The current clinical data, along with the contradictory results of a previous clinical study [ 35 ], imply that different clinical settings may determine the diverse effects of cilostazol treatment on PCSK9 expression, which may partly explain the inconclusive results regarding the effects of cilostazol on TC and LDL-C levels in previous clinical studies [ 19 , 20 , 34 , 35 , 36 ]. Despite the obesity-dependent effects of cilostazol on PCSK9 expression, we observed similar effects on the expression of AMPKα and PPARγ, suggesting that mechanisms beyond AMPK/PPARγ activation may be at play.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A previous study demonstrated the diverse effects of adipoR activation on PCSK9 expression in apoE-deficient (apoE −/− ) mice and wild-type mice [ 17 ]. The current clinical data, along with the contradictory results of a previous clinical study [ 35 ], imply that different clinical settings may determine the diverse effects of cilostazol treatment on PCSK9 expression, which may partly explain the inconclusive results regarding the effects of cilostazol on TC and LDL-C levels in previous clinical studies [ 19 , 20 , 34 , 35 , 36 ]. Despite the obesity-dependent effects of cilostazol on PCSK9 expression, we observed similar effects on the expression of AMPKα and PPARγ, suggesting that mechanisms beyond AMPK/PPARγ activation may be at play.…”
Section: Discussionmentioning
confidence: 88%
“…Circulating adiponectin concentrations are reduced in obese individuals, and this reduction has been proposed to play a crucial role in the pathogenesis of atherosclerosis and cardiovascular diseases associated with obesity and lipid metabolism [ 33 ]. We and others have demonstrated that cilostazol treatment can increase plasma adiponectin levels in patients with PAD [ 12 , 34 ]; however, the mechanisms of action were unknown. In the present study, we demonstrated that cilostazol treatment can enhance adiponectin expression in hepatocytes and that the adiponectin/adipoR/AMPK axis plays an important role in cilostazol-induced PCSK9 expression under normal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, in this study we found that plasma PCSK9 levels were reduced in poorly controlled patients as compared to well controlled patients. This finding could be partially explained by number of medications that could influence levels of plasma PCSK9 [27][28][29]. Several studies reported elevation of PCSK9 levels in diabetic patients [17,30].…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, a meta-analysis comparing triple antiplatelet therapy with dual therapy in patients with DM after PCI reported that triple therapy was associated with a lower risk of MACE despite MACE not being the primary endpoint in these trials [ 39 ]. Recently, we and other researchers have found that this compound has beneficial effects on metabolic parameters and vasculo-angiogenesis functions in diabetes, either bench or bedside [ 1 , 2 , 40 ]. Taken together, the DM subgroup analysis from our study, along with the results of previous studies in diabetes, implied that cilostazol might be a good choice of antiplatelet agent for diabetic patients with CAD or at a high risk of CV disease.…”
Section: Discussionmentioning
confidence: 99%